Drawing - the purpose - Duff, Leo; Sawdon, Phil (Play Text., 2008)
To clear their minds and organize their ideas, artists will often start projects by drawing sketches. Drawing? The Purpose asks why artists and designers use drawing in this way to kick-start their creative thinking, considering the application of drawing and its various uses across disciplines. From the interdisciplinary perspectives of archaeology, jewellery design, illustration and landscape architecture, this innovative volume highlights how drawing is used in the professional world. With examples from both contemporary and historical contexts, Drawing? The Purpose will be an invaluable.